Exercise intervention improves mitochondrial quality in non-alcoholic fatty liver disease zebrafish - Zou, Yun-Yi; Tang, Xiang-bin; Chen, Zhang-Lin; Liu, Bin; Zheng, Lan; Song, Ming-Yang; Xiao, Qin; Zhou, Zuo-Qiong; Peng, Xi-Yang; Tang, Chang-Fa (Frontiers in Endocrinology, 2023)
Introduction Recent reports indicate that mitochondrial quality decreases during non-alcoholic fatty liver disease (NAFLD) progression, and targeting the mitochondria may be a possible treatment for NAFLD. Exercise can effectively slow NAFLD progression or treat NAFLD. However, the effect of exercise on mitochondrial quality in NAFLD has not yet been established. Methods In the present study, we fed zebrafish a high-fat diet to model NAFLD, and subjected the zebrafish to swimming exercise. Results After 12 weeks, swimming exercise significantly reduced high-fat diet-induced liver injury, and reduced inflammation and fibrosis markers. Swimming exercise improved mitochondrial morphology and dynamics, inducing upregulation of optic atrophy 1(OPA1), dynamin related protein 1 (DRP1), and mitofusin 2 (MFN2) protein expression. Swimming exercise also activated mitochondrial biogenesis via the sirtuin 1 (SIRT1)/ AMP-activated protein kinase (AMPK)/ PPARgamma coactivator 1 alpha (PGC1α) pathway, and improved the mRNA expression of genes related to mitochondrial fatty acid oxidation and oxidative phosphorylation. Furthermore, we find that mitophagy was suppressed in NAFLD zebrafish liver with the decreased numbers of mitophagosomes, the inhibition of PTEN-induced kinase 1 (PINK1) – parkin RBR E3 ubiquitin protein ligase (PARKIN) pathway and upregulation of sequestosome 1 (P62) expression. Notably, swimming exercise partially recovered number of mitophagosomes, which was associated with upregulated PARKIN expression and decreased p62 expression. Discussion These results demonstrate that swimming exercise could alleviate the effects of NAFLD on the mitochondria, suggesting that exercise may be beneficial for treating NAFLD.